Erratum to “Small molecule inhibitors of mammalian glycosylation” [Matrix Biol. Plus 16C (2022) 100108] (Matrix Biology Plus (2022) 16, (S2590028522000084), (10.1016/j.mbplus.2022.100108)) - Almahayni, Karim; Spiekermann, Malte; Fiore, Antonio; Yu, Guoqiang; Pedram, Kayvon; Möckl, Leonhard (Matrix Biology Plus, 2022)
This article was temporarily removed in April 2022 due to production errors by the publisher. The publisher apologizes for any inconvenience caused.
CRIS-Team Scopus Importer:2024-09-09

Fluorophores’ talk turns them dark - Almahayni, Karim; Spiekermann, Malte; Möckl, Leonhard (Nature methods, 2022)
CRIS-Team Scopus Importer:2024-09-09

From Biophysics to Biomedical Physics - Almahayni, Karim; Bachir Salvador, Jana; Moonnukandathil Joseph, Dijo; Yurekli, Nazlican; Möllmert, Stephanie; Möckl, Leonhard (ACS Bio & Med Chem Au, 2024)
The intersection of physics and medicine has long been a fertile ground for innovation, with advances in one field driving breakthroughs in the other. In recent years, the emergence of modern biophysical techniques has provided a toolbox for understanding complex physiological processes across scales. These tools have the potential to revolutionize medical practice, from diagnosis to therapy. However, despite this immense potential, the path from basic biophysical research to clinical translation remains fraught with challenges. This review aims to highlight emerging biophysical tools and their potential applications in medical physics, with a focus on how these innovations can be translated into clinical solutions. We outline a strategic roadmap for bridging the gap between cutting-edge biophysics research and its effective integration into clinical settings, ensuring that these technologies can meaningfully transform patient care.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Biophysics; Clinical biology; Mechanical phenotyping; Medicine; Microscopy; Super-resolution microscopy; Translational medicine

RNA-binding proteins and glycoRNAs form domains on the cell surface for cell-penetrating peptide entry - Perr, Jonathan; Langen, Andreas; Almahayni, Karim; Nestola, Gianluca; Chai, Peiyuan; Lebedenko, Charlotta G.; Volk, Regan F.; Detrés, Diego; Caldwell, Reese M.; Spiekermann, Malte; Hemberger, Helena; Bisaria, Namita; et al. (Cell, 2025)
The composition and organization of the cell surface determine how cells interact with their environment. Traditionally, glycosylated transmembrane proteins were thought to be the major constituents of the external surface of the plasma membrane. Here, we provide evidence that a group of RNA-binding proteins (RBPs) is present on the surface of living cells. These cell-surface RBPs (csRBPs) precisely organize into well-defined nanoclusters enriched for multiple RBPs and glycoRNAs, and their clustering can be disrupted by extracellular RNase addition. These glycoRNA-csRBP clusters further serve as sites of cell-surface interaction for the cell-penetrating peptide trans-activator of transcription (TAT). Removal of RNA from the cell surface, or loss of RNA-binding activity by TAT, causes defects in TAT cell internalization. Together, we provide evidence of an expanded view of the cell surface by positioning glycoRNA-csRBP clusters as a regulator of communication between cells and the extracellular environment.
CRIS-Team Scopus Importer:2025-04-01
Keywords: cell surface; cell-penetrating peptides; glycoRNA; RNA-binding proteins

Setting the stage for universal pharmacological targeting of the glycocalyx - Almahayni, Karim; Möckl, Leonhard (Current Topics in Membranes, 2023)
All cells in the human body are covered by a complex meshwork of sugars as well as proteins and lipids to which these sugars are attached, collectively termed the glycocalyx. Over the past few decades, the glycocalyx has been implicated in a range of vital cellular processes in health and disease. Therefore, it has attracted considerable interest as a therapeutic target. Considering its omnipresence and its relevance for various areas of cell biology, the glycocalyx should be a versatile platform for therapeutic intervention, however, the full potential of the glycocalyx as therapeutic target is yet to unfold. This might be attributable to the fact that glycocalyx alterations are currently discussed mainly in the context of specific diseases. In this perspective review, we shift the attention away from a disease-centered view of the glycocalyx, focusing on changes in glycocalyx state. Furthermore, we survey important glycocalyx-targeted drugs currently available and finally discuss future steps. We hope that this approach will inspire a unified, holistic view of the glycocalyx in disease, helping to stimulate novel glycocalyx-targeted therapy strategies.
CRIS-Team Scopus Importer:2024-09-09
Keywords: cancer; Glycobiology; Glycocalyx; Pharmacology; Therapeutics; Vascular biology

Simple, Economic, and Robust Rail-Based Setup for Super-Resolution Localization Microscopy - Almahayni, Karim; Almahayni, Karim; Nestola, Gianluca; Spiekermann, Malte; Möckl, Leonhard (Journal of Physical Chemistry A, 2023)
Research during the past 2 decades has showcased the power of single-molecule localization microscopy (SMLM) as a tool for exploring the nanoworld. However, SMLM systems are typically available in specialized laboratories and imaging facilities, owing to their expensiveness as well as complex assembly and alignment procedure. Here, we lay out the blueprint of a sturdy, rail-based, cost-efficient, multicolor SMLM setup that is easy to construct and align in service of simplifying the accessibility of SMLM. We characterize the optical properties of the design and assess its capabilities, robustness, and stability. The performance of the system is assayed using super-resolution imaging of biological samples. We believe that this design will make SMLM more affordable and broaden its availability.
CRIS-Team Scopus Importer:2023-06-09

Small molecule inhibitors of mammalian glycosylation - Almahayni, Karim; Spiekermann, Malte; Fiore, Antonio; Yu, Guoqiang; Pedram, Kayvon; Möckl, Leonhard (Matrix Biology Plus, 2022)
Glycans are one of the fundamental biopolymers encountered in living systems. Compared to polynucleotide and polypeptide biosynthesis, polysaccharide biosynthesis is a uniquely combinatorial process to which interdependent enzymes with seemingly broad specificities contribute. The resulting intracellular cell surface, and secreted glycans play key roles in health and disease, from embryogenesis to cancer progression. The study and modulation of glycans in cell and organismal biology is aided by small molecule inhibitors of the enzymes involved in glycan biosynthesis. In this review, we survey the arsenal of currently available inhibitors, focusing on agents which have been independently validated in diverse systems. We highlight the utility of these inhibitors and drawbacks to their use, emphasizing the need for innovation for basic research as well as for therapeutic applications.
CRIS-Team Scopus Importer:2024-09-09
Keywords: Glycans; Glycocalyx; Glycosylation; Inhibitors; Small molecules

Tailored Bisacylphosphane Oxides for Precise Induction of Oxidative Stress-Mediated Cell Death in Biological Systems - Almahayni, Karim; Bachir Salvador, Jana; Conti, Riccardo; Widera, Anna; Spiekermann, Malte; Wehner, Daniel; Grützmacher, Hansjörg; Möckl, Leonhard (ACS Chemical Biology, 2024)
Precise cell elimination within intricate cellular populations is hampered by issues arising from the multifaceted biological properties of cells and the expansive reactivity of chemical agents. Current chemical platforms are often limited by their complexity, toxicity, and poor physical/chemical properties. Here, we report on the synthesis of a structurally versatile library of chemically tunable bisacylphosphane oxides (BAPOs), which harnesses the spatiotemporal precision of light delivery, thereby establishing a universal strategy for on-demand, precise cellular ablation in vitro and in viv
Keywords: Assays; Cells; Irradiation; Light; Toxicity

Treatment of acute myeloid leukemia models by targeting a cell surface RNA-binding protein - George, Benson M.; Eleftheriou, Maria; Yankova, Eliza; Perr, Jonathan; Chai, Peiyuan; Nestola, Gian Luca; Almahayni, Karim; Evans, Siân; Damaskou, Aristi; Hemberger, Helena; Lebedenko, Charlotta G.; Rak, Justyna; et al. (Nature Biotechnology, 2025)
Immunotherapies for acute myeloid leukemia (AML) and other cancers are limited by a lack of tumor-specific targets. Here we discover that RNA-binding proteins and glycosylated RNAs (glycoRNAs) form precisely organized nanodomains on cancer cell surfaces. We characterize nucleophosmin (NPM1) as an abundant cell surface protein (csNPM1) on a variety of tumor types. With a focus on AML, we observe csNPM1 on blasts and leukemic stem cells but not on normal hematopoietic stem cells. We develop a monoclonal antibody to target csNPM1, which exhibits robust anti-tumor activity in multiple syngeneic and xenograft models of AML, including patient-derived xenografts, without observable toxicity. We find that csNPM1 is expressed in a mutation-agnostic manner on primary AML cells and may therefore offer a general strategy for detecting and treating AML. Surface profiling and in vivo work also demonstrate csNPM1 as a target on solid tumors. Our data suggest that csNPM1 and its neighboring glycoRNA–cell surface RNA-binding protein (csRBP) clusters may serve as an alternative antigen class for therapeutic targeting or cell identification.
CRIS-Team Scopus Importer:2025-05-02